Implementation of Shafi’i Fiqh in Brunei’s Halal Law for Meat and Poultry Products - binti Abdul Mahmod, Nur Hafizah; bin Mahmud, Hafini (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Abstract: Islamic Halal Law in the Shafi'i school in Brunei Darussalam is firmly rooted in the country's constitution, which stipulates the Shafi'i school as the basis of Islamic law, including meat and poultry products. This article analyzes the application of the fiqh of the Shafi'i madhhab in the Brunei Darussalam halal legal system, especially in meat and poultry products. This research is normative juridical. Data collection is carried out through a study of halal regulations in Brunei Darussalam and through literary studies of books or articles on halal, especially in fiqh and legal studies. The collected data were analyzed descriptively. This study concludes that, constitutionally, Brunei establishes the Shafi'i school as the basis for binding Islamic law in the formulation of laws, including the Halal Meat Law (Article 183) and the Halal Certification and Labeling Order 2005. The application of Shafi'i fiqh in Brunei is carried out through three models: textual adoption of fiqh law, substantive adaptation in industrial technical standards, and modern ijtihad to contemporary issues such as stunning and basmalah reading. The principle of halalan ṭayyiban translates into a strict system of sanitary supervision, certification, and halal audits. This application reflects the harmonization between classical Islamic law and modern needs by maintaining the maqāṣid al-sharī'ah, in particular ḥifẓ al-dīn and ḥifẓ al-nafs. The Brunei model shows that Shafi'i fiqh can be institutionalized in a contemporary way without losing its theological authenticity and ethical foundations in sharia. Keywords: Fiqh Shafi'i, halal law, meat, poultry, regulations.   Abstrak: Hukum Halal Islam dalam mazhab Syafi’i di Brunei Darussalam berakar kuat pada konstitusi negara yang menetapkan mazhab Syafi’i sebagai dasar perundangan Islam, termasuk produk daging dan unggas. Artikel ini menganalisis penerapan fiqh mazhab Syafi’i dalam sistem hukum halal Brunei Darussalam, khususnya pada produk daging dan unggas. Penelitian ini adalah yuridis normatif. Pengumpulan data dilakukan melalui studi regulasi halal di Brunei Darussalam dan studi literer dari buku atau artikel yang membahas tentang halal, khususnya dari kajian fikih dan hukum. Data yang terkumpul dianalisis secara deskriptif. Penelitian ini menyimpulkan bahwa secara konstitusional, Brunei menetapkan mazhab Syafi’i sebagai dasar hukum Islam yang mengikat dalam pembentukan undang-undang, termasuk Halal Meat Law (Pasal 183) dan Halal Certification and Labeling Order 2005. Penerapan fiqh Syafi’i di Brunei dilakukan melalui tiga model: adopsi tekstual terhadap hukum fiqh, adaptasi substantif dalam standar teknis industri, dan ijtihad modern terhadap isu kontemporer seperti pemingsanan (stunning) dan pembacaan basmalah. Prinsip halalan ṭayyiban diterjemahkan menjadi sistem pengawasan kebersihan, sertifikasi, dan audit halal yang ketat. Penerapan ini mencerminkan harmonisasi antara hukum Islam klasik dan kebutuhan modern dengan mempertahankan maqāṣid al-sharī‘ah, khususnya ḥifẓ al-dīn dan ḥifẓ al-nafs. Model Brunei menunjukkan bahwa fiqh Syafi’i dapat diinstitusionalisasi secara modern tanpa kehilangan otentisitas teologis dan etika syariah. Kata Kunci: Fiqh Syafi’i, hukum halal, daging, unggas, regulasi